Molecular association studies in predicting risk of advanced liver disease in HBV infected patients / Behnaz Riazalhosseini - Behnaz , Riazalhosseini (2017)
Hepatitis B virus infection (HBV) is a serious public health problem and a risk factor for liver cirrhosis and hepatocellular carcinoma (HCC). Globally it affects more than 2 billion individuals and over 600,000 persons die annually due to the consequence of the disease. In this study, we aim to investigate association between genetic polymorphisms of various candidate genes, of microRNAs expression as well as of HLA-DQ gene and risk of progression of HBV infection to cirrhosis / HCC in a Malaysian population. A total of 526 subjects were enrolled in this study. The participants were made up of 423 chronic HBV patients without cirrhosis/HCC and 103 chronic HBV patients with cirrhosis /HCC. Genotyping of 19 SNPs from 10 genes was carried out using Sequenom MassARRAY® platform. The microRNA profiling was performed using Affymetrix GeneChip® miRNA 3.0 Array. The HLA typing of HLA-DQA1 and HLA–DQB1 was done using the LAB Type PCR- sequence specific oligonucleotide (PCR-SSO) probes technique and Luminex profiling system. Data was analyzed using SPSS version 16.0 statistical software. The microarray results were analyzed using Expression console software, Transcriptome Analysis Console (TAC) and the Ingenuity Pathway Analysis (IPA) software. The raw data from Luminex were analyzed by HLA Fusion software. The result of genetic association study showed that rs12304647 of microRNA-196A2 has a protective effect from progression to cirrhosis/HCC (OR=0.37, 95% CI=0.15 - 0.89, p=0.027). The results of miRNA profiling revealed that six miRNAs were up-regulated (miRNA-935, miRNA342-5p, miRNA- 339, miRNA- 4508, miRNA- 3615 and miRNA-3200-5p) while two down-regulated (miRNA-182 and miRNA-4485) between the HBV with and without cirrhosis/HCC groups (fold change ≥ 2 or ≤ -2, p-value ≤ 0.05). The results of HLA typing revealed the presence of five HLA-DQA1 alleles (-DQA1*01, -DQA1*02, -DQA1*03, - DQA1*05 and -DQA1*06) and five HLA-DQB1 alleles (-DQB1*02, -DQB1*03, - DQB1*04, -DQB1*05 and -DQB1*06). Among all patients in this study, 66% of HBV iv patients with cirrhosis / HCC and 62% of HBV patients without cirrhosis / HCC are carries of HLA-DQA1*01 (p value= 0.908, OR= 0.95, CI= 0.41 - 2.10). Moreover, 73% of HBV patients with cirrhosis / HCC and 60% of HBV patients without cirrhosis / HCC are carries of HLA-DQB1*03 (p value= 0.320, OR= 1.56, CI= 0.65 - 3.72). In summary, this study showed that there is a significant association between microRNA196A2 rs12304647 gene and reduced risk of progression to cirrhosis/HCC in patients with chronic HBV infection. In addition, the eight identified microRNAs may have a significant clinical value in diagnosis of progression of disease in HBV infected patients. However, no significant association was found between the identified HLA-DQ alleles and progression of HBV to cirrhosis and HCC.